Planning Development Level of Evidence Pain Management in Pre-hospital Emergency Department: A Systematic Review - Fany Arsyad Hidayaturachman; Djazuly Chalidyanto; Dewi Retno Suminar (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: Regarding pre-hospital pain management focus on the emergency department, safety of analgesics used is one of the concerned areas to be developed clearly. However, the current level of evidence in pre-hospital pain management of injured patients, focusing on the safety and effect of pre-hospital analgesia has not been explored. The aim of this study was to analyze the level of evidence in pre-hospital pain management of injured patients, focusing on the safety and effect of pre-hospital analgesia. Methods: A systematic review was performed in this study with inclusion criteria adult-elderly injured patients in pre-hospital setting and used analgesic agents. Articles were sourced from electronic database Scopus, PubMed, Science Direct, Springer Link and ProQuest, which were searched to identify all the relevant articles published over the last five years in English. Fifteen studies were included are qualified as articles assessment with Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. Results: Nine studies were Randomized Control Trial, two studies cross-sectional and retrospective, and one study prospective descriptive and cohort. The result showed that many types of analgesic are used or planned in emergency areas, such as morphine, ketamine, fentanyl, NSAID with different route intravenous, intramuscular and subcutaneous with safety and monitoring continuously by healthcare professionals. Conclusion: The use of pre-hospital analgesia for injured patient in pre-hospital setting is commonly used by health workers according to pain management standard and guidelines; planning developments are needed for safety and management as a concern for focus on quality of pain management status.